Profit Analysis of Pig Farmers on a Smallholder Scale in West Kakas, Minahasa - Herman Adrian Lexi Tiwow; Ni Made Ayu Gemuh Rasa Astiti; Eusebius KM Endoh (Agriwar Journal, 2024)
This study aims to determine the cost, income, and profit of small-scale pig farming in West Kakas Sub District, Minahasa District, North Sulawesi, Indonesia. The number of respondents in this study amounted to 30 people carried out in three villages including Touliang village, Wasian village, and Simbel village which was carried out during January 2021. Data collection using primary data through direct interviews with respondents with questions that have been prepared, and secondary data obtained from the sub-district office and related agencies. The determination of the sample for the research location was carried out using the purposive sampling method or carried out deliberately based on the criteria for length of business, business character, and the number of livestock and the scale of smallholder businesses run by farmers. The method used in this research is descriptive analysis to describe the pig farming business in the West Kakas Subdistrict, and the amount of R / C of the pig farming business in the West Kakas Subdistrict during one maintenance period. The results of this study show that: 1). The amount of costs incurred by pig farmers in the western Kakas sub-district is IDR.296,523,750 with an average cost per farmer of IDR.9,884,125 during one maintenance period, so the income earned is IDR.385,300,000 with an average revenue per farmer of IDR.12,843,333, during one maintenance period, so that the profit earned by farmers is IDR.88,776,250 with an average profit per farmer of IDR.2,959,208 per maintenance period. R / C on pig farms in the sub-district of West Kakas, Minahasa District is 1.29, meaning that if the costs incurred by the farmer are IDR. 1.00, the revenue is IDR.1.29 and the profit income is IDR. 0.29. So, the pig farming business in West Kakas District, Minahasa District is profitable.